Neutralizing antibody evasion and transduction with purified extracellular vesicle-enveloped adeno-associated virus vectors - Cheng, Ming; Dietz, Laura; Gong, Yi; Eichler, Florian; Nammour, Josette; Ng, Carrie; Grimm, Dirk; Maguire, Casey A. (Human gene therapy, 2021)
Adeno-associated virus (AAV) is classified as a nonenveloped DNA virus. However, several years ago, we discovered that in media of packaging cells producing recombinant AAV vectors, AAV capsids can associate with the interior and surface of extracellular vesicles (EVs), sometimes referred to as exosomes. Since then, we and others have demonstrated that exosome-enveloped AAV, exo-AAV, can enhance transduction in vivo as well as evade neutralizing antibodies. - - While promising, these data were generated with differential centrifugation to pellet the exo-AAV. This method results in a heterogeneous mixture of exo-AAV, coprecipitating proteins, as well as free AAV capsids. To define the properties of exo-AAV more accurately, in this study, we used a density gradient method to purify exo-AAV. We next performed head-to-head comparisons of standard AAV1, differential centrifuged exo-AAV1, and gradient purified exo-AAV1 for antibody evasion and transgene expression in the murine brain. We found purified exo-AAV1 to be more resistant to neutralizing antibodies than the other AAV preparations. Direct intracranial injection of purified exo-AAV1 into mice resulted in robust transduction, which transduced a larger area of brain than standard AAV1. We also identified the recently described membrane-associated accessory protein by mass spectrometry of purified exo-AAV1 preparations. Finally, we used a scalable method, size-exclusion chromatography to isolate exo-AAV1, and demonstrated functional transduction in cultured cells and increased antibody resistance. Together, these data suggest that higher purity exo-AAV will have beneficial characteristics for gene delivery and also may lead to mechanistic insights into the incorporation of AAV into EVs.
Online ahead of editing: August 27, 2021
Gesehen am 27.01.2022